Νανομηχανικός χαρακτηρισμός κελυφών: μαθήματα σχεδιασμού από τη φύση - Καρυού, Μαρία (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
The rapid advancement of manufacturing technology currently allows material design to originate from the microscopic level of microstructures to the macroscopic level where materials are employed in engineering applications. In certain applications, such as protective coatings, biological implants, etc., the designer attempts to optimize the material for its mechanical response. Since the macroscopic material properties (mechanical, optoelectronic, thermal, etc.) directly depend on the microstructure (chemical composition, morphology, constituent properties) we seek to choose the microstructure that will give the best macroscopic properties for the particular application. During the materials design process, on many occasions ideas might originate from nature which has evolutionary optimized natural materials throughout the years. This process forms the fundamental basis of biomimetics which formed the main impetus for embarking on this dissertation thesis. The main scope of this research is the systematic study of sea shells for understanding the characteristics that underpin their excellent mechanical properties, which have been evolutionary developed through the years in order to protect the living organisms that reside within them from the rest of the sea kingdom. The mechanical, morphological and chemical properties of nine different shells by the Cyprus Mediterranean coast have been characterized. After a literature review on the subject, the collection and identification of shells has followed. The morphological features of the microstructure were investigated by Scanning Electron Microscopy (SEM), the stoichiometry with Energy-dispersive X-ray spectroscopy (EDX) and the mechanical properties by instrumented nanoindentation. During this work the operating principles and the theoretical background for the collection and analysis of data has been studied in depth. It appears that the shells consist of aragonite plates that are either stacked in layers with reinforcing organic material in between or consisting of fiber/organic material nanocomposites. The brick and mortar morphology appears to provide harder arrangements. Furthermore, the high content of calcium in combination with the increased amount of organic protein appears to be the main reason that the shells become hard and durable.
Keywords: Biomimetic; Sea Shells; Nanoindentation; Βιομιμητική; Θαλάσσια Κελύφη; Νανοδιείσδυση